Drug interactions in the pharmacotherapy of patients included in primary care comprehensive medication management services - Hágabo M. SILVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: A drug interaction (DI) is the clinical event in which the effect or action of one drug is modified by the presence of another. Because of potential harms and low consistency of available information, it is critical to assess the clinical relevance of DI. This study aimed to identify and evaluate the clinical consequences of DI in the pharmacotherapy of patients followed in a primary care Comprehensive Medication Management (CMM) services. Methods: This observational cross-sectional study was based on the analysis of the CMM records all the patients that used at least two medications and attended to at least three CMM consultations from August 2015 to March 2016 (n=88). Potential DI were identified among the medications used in the initial consultation of CMM using Micromedex® Drug-Reax® software. The DI were classified as “monitorable” (when its clinical consequences could be monitored by effectiveness or safety paremeters) or non-monitorable, and their clinical consequences were evaluated by analysis of CMM records. Results: Among the studied population 95.5% of the patients had at least one potential DI in their pharmacotherapy, totaling 493 potential DI. Of all the potential DIs identified, 90.9% were monitorable, and the majority of these monitorable DI presented no clinical consequences (62.7%). For 63.9% of the DI with clinical impact, the pharmacist adopted direct or indirect measures that would favor the resolution or reduction of the clinical impact of DIs. Conclusion: The CMM service facilitates the management of DIs since its decision-making method calls for monitoring of the effectiveness and safety parameters, individualizing the management of DIs according to the patient’s needs and their clinical consequences.